Baula ; Postal service Mga kuwento ng Apo - Lazaro, Cheche (The Probe Team, 1988)
Col. Francisco Baula, Jr., an AFP soldier who is confined to the stockade, is killed by Stockade guards, allegedly for trying to escape. Looks at the complaints about the postal service in the Philippines. The Apo Hiking Society, the singing trio talks about their songs, philosophers and concerns.